High-performance computing and big data analysis : second International Congress, TopHPC 2019, Tehran, Iran, April 23-25, 2019, Revised selected papers /: second International Congress, TopHPC 2019, Tehran, Iran, April 23-25, 2019, Revised selected papers. (2019) - Unknown
No abstract available